A MATTER of FACTS : The Value of Evidence in an Information Age /? - Millar, Laura, 1959- (Archival futures)
A Matter of Facts: The Value of Evidence in an Information Age highlights the critical value of records and archives as sources of evidence: as vital tools for supporting human rights and enforcing public responsibilities across society--